2022
DOI: 10.3390/healthcare10020207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training on Skin Temperature and Its Relationship with Central Nervous System (CNS) Activation

Abstract: The aim of this work was to relate the activation of the sympathetic and parasympathetic nervous systems with the skin temperature (Tsk) of the lower limbs after a resistance training exercise. Under controlled conditions, the average Tsk in the areas of the anterior and posterior thighs, knees and legs was obtained with a thermal imager and the parasympathetic and sympathetic activation was registered with an Omegawave® device on 20 healthy and trained male volunteers (25.39 ± 8.21 years) before exercise, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, we elaborated a normative table to establish the thermal profile of the adolescents based on the %BF for each ROI analyzed. For this, we used the percentiles (P) as a reference to classify if an ROI was "strongly hypo-radiant" (P < 5), "hypo-radiant" (P The thermograms were automatically analyzed with ThermoHuman ® software version 2.12 (PEMA THERMO GROUP S.L., Madrid, Spain), a validated system [30,31] that has been used in other studies with human population [32][33][34]. The software provides mean Tsk and standard deviation values and the number of pixels, which are automatically quantified in 48 ROI for the upper body and 36 ROI for the lower body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we elaborated a normative table to establish the thermal profile of the adolescents based on the %BF for each ROI analyzed. For this, we used the percentiles (P) as a reference to classify if an ROI was "strongly hypo-radiant" (P < 5), "hypo-radiant" (P The thermograms were automatically analyzed with ThermoHuman ® software version 2.12 (PEMA THERMO GROUP S.L., Madrid, Spain), a validated system [30,31] that has been used in other studies with human population [32][33][34]. The software provides mean Tsk and standard deviation values and the number of pixels, which are automatically quantified in 48 ROI for the upper body and 36 ROI for the lower body.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 min, following the methodology of Yasuoka et al [29], they were asked to report the thermal sensation (TS) on a 9-point scale (+4, very hot; +3, hot; +2, warm; +1, slightly warm; 0, neutral; −1, slightly cool; −2, cool; −3, cold; −4 very cold) and the comfort sensation (CS) on a 7-point scale (+3, very comfortable; +2, comfortable; +1, slightly comfortable; 0, neutral; −1, slightly uncomfortable; −2, uncomfortable; −3, very uncomfortable). The thermograms were automatically analyzed with ThermoHuman ® software version 2.12 (PEMA THERMO GROUP S.L., Madrid, Spain), a validated system [30,31] that has been used in other studies with human population [32][33][34]. The software provides mean Tsk and standard deviation values and the number of pixels, which are automatically quantified in 48 ROI for the upper body and 36 ROI for the lower body.…”
Section: Thermography Assessmentmentioning
confidence: 99%
“…Strength training normally uses larger, high-intensity loads, which would affect movement velocity, promote hormonal changes, and change local temperature [ 10 , 11 , 12 , 13 ], leading to thermal changes and increased fatigue [ 14 , 15 ] and a consequent increase in movement asymmetry [ 16 ]. Previous studies reported that fatigue would be associated with greater asymmetries in movement and thermals, with a consequent increase in the risk of injuries [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%